2019
DOI: 10.3991/ijim.v13i07.10654
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Using Digital Smart Board to Enhance Primary School Students’ Learning

Abstract: Digital smart board is one of interactive technology tools which has been used widely in schools to facilitate teaching and learning. Empirical evidence shows that digital smart board allows students to construct their knowledge while mastering more advanced thinking skills. Thus integration of digital smart board facilitates active learning, which is fundamental to mastery of skills. Active learning using smart board program is a program which integrates smart board in Data Handling so that primary school stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…The level of feasibility of thematic-integrative insructional assets in the method of digital comics with human and environmental interaction material is known through validation by expert material, validation by media experts, validation by teachers and trial use by students. Borg and Gall [22] explained the ten steps of implementing the research and development strategy as follows:…”
Section: Development Modelmentioning
confidence: 99%
“…The level of feasibility of thematic-integrative insructional assets in the method of digital comics with human and environmental interaction material is known through validation by expert material, validation by media experts, validation by teachers and trial use by students. Borg and Gall [22] explained the ten steps of implementing the research and development strategy as follows:…”
Section: Development Modelmentioning
confidence: 99%
“…In research conducted by [9] on 30 students implicated that active learning using smart board program was effective in enhancing primary school students" learning performance in Data Handling. Other areas of research works engaging smart board include [5] on tertiary students and [10] on social studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The expression of high degree of usage reflected that smart board was valued highly in instruction by a large majority of teachers. 75% of classrooms in England adopted the technology [9] has likely set a benchmark for the accessibility of the technology if quality education is aimed to be achieved. The researched school had the smart board available in its classes, and the teachers utilised them to a sufficient degree.…”
Section: A the Acceptance Level Of Using Smart Board By Teachers In Primary Schoolmentioning
confidence: 99%
“…Studies investigating the benefits of using technology in the classroom have increased in the last few years. Their collective findings reported that the application of technology in education could improve student anger management skills, enhance the teaching-learning process's effectiveness, increase academic achievement, and foster positive behavior [7][8][9][10][11][12][13]. Other studies presented that the application of technology can raise problem-solving capability, heighten computational thinking competency, upgrade writing ability, be adopted due to usefulness and easiness, and boost motivation [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%